Rilonacept maintains long-term inflammatory remission in patients with deficiency of the IL-1 receptor antagonist - Garg, Megha; de Jesus, Adriana A.; Chapelle, Dawn; Dancey, Paul; Herzog, Ronit; Rivas-Chacon, Rafael; Muskardin, Theresa L. Wampler; Reed, Ann; Reynolds, James C.; Goldbach-Mansky, Raphaela; Sanchez, Gina A. Montealegre (JCI insight, 2017)
Deficiency of IL-1 receptor antagonist (DIRA) is a rare autoinflammatory disease that presents with life-threatening systemic inflammation, aseptic multifocal osteomyelitis, and pustulosis responsive to IL-1-blocking treatment. This study was performed (a) to investigate rilonacept, a long-acting IL-1 inhibitor, in maintaining anakinra-induced inflammatory remission in DIRA patients, (b) to determine doses needed to maintain remission, and (c) to evaluate the safety and pharmacokinetics of rilonacept in young children (<12 years). Six mutation-positive DIRA patients (children, ages 3-6 years), treated with daily anakinra, were enrolled into an open-label pilot study of subcutaneous rilonacept for 24 months. Clinical symptoms and inflammatory blood parameters were measured at all visits. A loading dose (4.4 mg/kg) was administered, followed by once weekly injections (2.2 mg/kg) for 12 months. Dose escalation (4.4 mg/kg) was allowed if inflammatory remission was not maintained. Subjects in remission at 12 months continued rilonacept for an additional 12 months. Five of six patients required dose escalation for findings of micropustules. Following dose escalation, all patients were in remission on weekly rilonacept administration, with stable laboratory parameters for the entire study period of 24 months. All children are growing at normal rates and have normal heights and weights. Quality of life improved while on rilonacept. No serious adverse events were reported. Rilonacept was found to maintain inflammatory remission in DIRA patients. The once weekly injection was well tolerated and correlated with increased quality of life, most likely related to the lack of daily injections. ClinicalTrials.gov NCT01801449. NIH, NIAMS, and NIAID.